PENGARUH STRUKTUR KEPEMILIKAN, STUKTUR GOOD CORPORATE GOVERNANCE, EARNINGS MANAGEMENT DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK - Rando Winanto, (2017)
This study was conducted to examine the effect of variabel Family Ownership, Board of Directors, Audit Commitee, Earnings Management, and Corporate Social Responsibility Disclosure on Tax Aggressiveness by proxy Effective Tax Rate (ETR) which is ratio of taxation on income, and Cash Effective Tax Rate (CETR) the payment of tax liabilities on income in manufacturing companies in Indonesian Stock Exchange period 2013-2015. Samples were obtained in this study of 45 companies listed in the selected using purposive sampling method. After eleminating the outliers data, which eventually resulted 96 ovservations that ready to be analyzed and tested with Tax Aggresiveness (ETR) and 76 observatons with (CETR). The analysis technique used is the multiple liniear regression with a probability level of 5%. These results indicate that the Family Owniership not significant effect on Tax Aggresiveness (ETR) and (CETR), Board of Directors a significant effect on Tax Aggresiveness (ETR), but not significant effect on Tax Aggresiveness (CETR), Audit Commitee not significant effect on Tax Aggresiveness (ETR) and (CETR), Earnings Management not significant effect on Tax Aggresiveness (ETR) and (CETR), and Corporate Social Responsibility Disclosure not significant effect on Tax Aggresiveness (ETR), but significant effect on Tax Aggresiveness (CETR).